Investigation of the hydrodynamic impacts of aquaculture structures on inland shallow water the case of Laguna de Bay - Pangyarihan, Ronalie F.
Laguna Lake, the largest freshwater inland body in the Philippines, is strategically located in the center of urbanize municipalities from National Capital Region and Region VIA. Because of the high demands from the populated regions, the lake has been utilized for many kinds of uses but the dominant use of the lake is for aquaculture. Aquaculture may have significant impacts on the hydrodynamics of a water body. The main objective of this study is to assess the effects of aquaculture structures in the lake hydrodynamics. The current set-up of fish pens and cages as prescribed by the Laguna Lake Development Authority was studied. Correspondingly, this research recommends an ideal layout of fish pens and cages through analysis of results of hydrodynamic modeling. The modeling software Delft3D-FLOW was used in the creation of the lake hydrodynamic model. Primary driving factors controlling lake hydraulics and water balance of the lake were considered in the model. Aquaculture structures were mathematically represented in the model as local weirs with a specified friction loss term (0.6). Considering the research dealt with a large environmental system, calibration was done in terms of the bed roughness coefficients. The calibration parameters used were the roughness for Pasig River (n=0.039) and roughness for the lake (0.020). Considering all assumptions and limitations, scenario simulation analysis revealed that the 17% area allocation for the fish pens and cages in the lake has minimal effects on the hydrodynamics in a bay-wide scale, but with more localized significance. The most recommendable scenario among all the generated layout was found out to be the one with no fish pens and cages located adjacent to the shoreline. The recommended layout has less risk in terms of eutrophication and sediment deposition problems based on the current velocity patterns. All findings from this research were solely based on the analysis of the lake hydrodynamics. This study may serve as an aid to future ecological assessments about Laguna Lake.